TINJAUAN YURIDIS HOLDINGISASI BUMN DALAM RANGKA PENINGKATAN KINERJA MENURUT PERSPEKTIF HUKUM PERUSAHAAN - JOHN SIPAYUNG; BISMAR NASUTION; MAHMUL SIREGAR (TRANSPARENCY, 2013)
The government will implement  holding  process  in plantation  sector  in this year. However, the hindrance found in this holding process is the  unavailability of  specific regulation  governing  the  forming of  holding in company. Having this  holding, it will  improve the performance  of the company  and  add the  profit  from new  company  with the  holding. The  objective of this research  is to know  the role of the  government  in implementing the forming of  holding  company. The method  of research was  analysis  descriptive  research method, that was  a research describing  a situation  or event  to search, and  then to  analyze  the  event based on the facts  from the secondary data  obtained from  primary  law  material,  secondary  law material  and  tertiary  law material.  The used  research method was  yuridical normative  analysis, that was  by  describing and  testifying  the  data related to  the problem in  company  holding.  Data  collection  technique for  this research  was carried  out  with  library  research,  literature  or  documents to  get the secondary data. The existence of state-owned corporations is one of real forms in  Constitution 1945 especially article  33  with strategic  position  to increase the  prosperity of the people.  In the case of  holding  company that the responsibility  of main  company  to branch company is  only limited to  the authority  given   to main company.  The  responsibility is only on  management and policies related to the  branch  companies.  Hence,  it is necessary to have one  rule  governing  the  holding in  specific and the  government  may understand and  know  the real process of the  holding  in  state  owned  corporations. It is intended  to  improve the  performance of  state  owned  corporations  related to the  income and  expenditure of  state. Kata Kunci : BUMN, Holding, dan Hukum Perusahaan.